Theoretical discussions of biography : approaches from history, microhistory, and life writing - Renders, Hans; Haan, Binne de (Brill, 2014)
"Theoretical Discussions of Biography: Approaches from History, Microhistory, and Life Writing offers comprehensive overviews by 14 academic scholars of the actual state of the field of Biography Studies, specifically by connecting biography with microhistory, journalism, and Life Writing." -- Resumé vydavatele
Keywords: biografie; historiografie; autobiografie; biography; historiography; autobiography; sborníky; elektronické knihy; papers of several authors; electronic books